The Major Factors Affecting Oocyte Quality in IVF Cycles: A Narrative Review - Boueri, Myriam; Saliba, Marita; Haydamous, Joe; Amanzo Vargas, Maria Pia; Hamam, Yaser; Al Ashkar, Rana; Nicolas Moujally, Sophie; Maqbool, Shahzaib; El Bab, Hala; Mourad, Ali; Albaini, Obey (International Journal of Clinical Research, 2023)
Background: The role of assisted reproductive technologies, including in-vitro fertilization [IVF], is increasing daily because of the significant rise in subfertility cases. Among women, the most observed causes of infertility are primary ovarian insufficiency and premature ovarian failure, accounting for 25% of cases, followed by tubal damage (20%) and uterine abnormalities (10%), all contributing to the increase in IVF cases among couples. The success of IVF depends on various factors; however, the role of oocyte quality and maturation level is considered a pivotal cardinal factor for the success rates of IVF. Methods: A thorough literature analysis was performed using the following search terms: “Oocyte Quality” and “IVF cycle.” The databases searched included PubMed, Google Scholar, MEDLINE, Cochrane Library, and ResearchGate. Discussion: IVF success rates especially depend on oocyte quality and level of maturation. Several factors affecting these two factors include obesity, which increases O2 and H2O2 levels resulting in elevated endoplasmic reticulum [ER] stress; Polycystic Ovary Syndrome [PCOS]; age; endometriosis; cyclic nucleotides used in IVF; thalassemia major which is associated with lower ovarian reserve and increased redox activity malignancies, and anti-neoplastic drugs, which may contribute to premature ovarian insufficiency. Various treatment options were proposed to improve oocyte quality and maturation level, including growth hormone [GH] supplementation alongside ovarian supplementation, autologous mitochondrial transfer, luteal phase ovarian stimulation, administration of MI-Melatonin-Vitamin D3, Duphaston, and putrescine supplementation. Conclusion: With the rising number of subfertility cases, the importance of Assisted Reproductive Technologies [ART] is growing. The success rate of IVF on oocyte quality and level of maturation level, and few with several factors affecting these. Though numerous treatment options have been proposed to enhance oocyte quality and maturation, not all have been deemed beneficial.